Brain-Type Glycogen Phosphorylase Is Crucial for Astrocytic Glycogen Accumulation in Chronic Social Defeat Stress-Induced Depression in Mice - Zhu, Yuanyuan; Fan, Ze; Zhao, Qiuying; Li, Jiaqi; Cai, Guohong; Wang, Rui; Liang, Yi; Lu, Naining; Kang, Junjun; Luo, Danlei; Tao, Huiren; Li, Yan; et al. (Frontiers in Molecular Neuroscience, 2022)
Astrocytic glycogen plays an important role in brain energy metabolism. However, the contribution of glycogen metabolism to stress-induced depression remains unclear. Chronic social defeat stress was used to induce depression-like behaviors in mice, assessed with behavioral tests. Glycogen concentration in the medial prefrontal cortex (mPFC) and the expression of key enzymes of the glycogen metabolism were investigated using Western blots, immunofluorescent staining, electron microscopy, and biochemical assays. Stereotaxic surgery and viral-mediated gene transfer were applied to knockdown or overexpress brain-type glycogen phosphorylase (PYGB) in the mPFC. The glycogen content increased in the mPFC after stress. Glycogenolytic dysfunction due to inactivation of PYGB was responsible for glycogen accumulation. Behavioral tests on astrocyte-specific PYGB overexpression mice showed that augmenting astrocytic PYGB reduces susceptibility to depression when compared with stress-susceptible mice. Conversely, PYGB genetic down-regulation in the mPFC was sufficient to induce glycogen accumulation and depression-like behaviors. Furthermore, PYGB overexpression in the mPFC decreases susceptibility to depression, at least partially by rescuing glycogen phosphorylase activity to maintain glycogen metabolism homeostasis during stress. These findings indicate that (1) glycogen accumulation occurs in mice following stress and (2) glycogenolysis reprogramming leads to glycogen accumulation in astrocytes and PYGB contributes to stress-induced depression-like behaviors. Pharmacological tools acting on glycogenolysis might constitute a promising therapy for depression.